2018
DOI: 10.1086/697224
|View full text |Cite
|
Sign up to set email alerts
|

Chronological and Biological Age Predict Seasonal Reproductive Timing: An Investigation of Clutch Initiation and Telomeres in Birds of Known Age

Abstract: Female vertebrates that breed earlier in the season generally have greater reproductive success. However, evidence suggests that breeding early may be costly, thus leading to the prediction that females with fewer future reproductive events will breed earlier in the season. While chronological age is a good indicator of remaining life span, telomere lengths may also be good biomarkers of longevity as they potentially reflect lifetime wear and tear (i.e., biological age). We examined whether variation in the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…However, this trend is not consistent amongst all birds, with some species showing increases in TRF with age, as in the Leach's storm‐petrel ( Oceanodroma leucorhoa ) (Haussmann et al, ), and no decline in length, or both as reported for the Magellanic penguin ( Spheniscus magellanicus ) (Cerchiara et al, ). For individuals in some avian species, change in telomere length can be tracked longitudinally and correlate with reproductive timing; however, the use of TRF for cross‐sectional analysis of age has yet to be demonstrated (Bauer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this trend is not consistent amongst all birds, with some species showing increases in TRF with age, as in the Leach's storm‐petrel ( Oceanodroma leucorhoa ) (Haussmann et al, ), and no decline in length, or both as reported for the Magellanic penguin ( Spheniscus magellanicus ) (Cerchiara et al, ). For individuals in some avian species, change in telomere length can be tracked longitudinally and correlate with reproductive timing; however, the use of TRF for cross‐sectional analysis of age has yet to be demonstrated (Bauer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR (qPCR) was used to measure relative telomere length in extracted samples with respect to a single‐copy control gene (glyceraldehyde‐3‐phosphate dehydrogenase, GAPDH ) (Criscuolo et al, ), following methods adapted for the dark‐eyed Junco (Bauer et al, ). GAPDH primer sequences were as follows: forward GAPDH (5’‐AACCAGCCAAGTACGATGACAT‐3′) and reverse GAPDH (5′‐CCATCAGCAGCAGCCTTCA‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…A standard curve (40, 20, 10, 5 and 2.5 ng) from a single reference sample was run in triplicate on every plate to control for interplate variation (Schmidt et al, ). These values were chosen because they consistently produce reactions with optimal efficiencies (Bauer et al, ; Schmidt et al, ). The curve was made by mixing red blood cell samples from six one‐year‐old male dark‐eyed juncos and extracting DNA from the pooled sample four times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason that early-47 life conditions have often been observed to influence the functioning of the adult stress response may be 48 that early-life conditions can speed up or slow down the biological ageing process, and consequently 49 advance or retard age-related shifts in the functioning of the stress response system. A potential marker of 50 biological age is the attrition of telomeres, the DNA caps at the ends of linear chromosomes (Bize et al, 51 2009;Bauer et al, 2018), with more lifetime attrition indicating greater biological age. The rate of 52 telomere attrition is much higher during the developmental period than in adulthood, and has been shown 53 to be accelerated by early-life adversity (Boonekamp et al, 2014;Nettle et al, 2015 Nettle et al, , 2017.…”
mentioning
confidence: 99%